"We at least say we are equal": Gender equality and class in healthcare professionals' discursive framing of migrant mothers. (July 2021) - Símonardóttir, Sunna; Rúdólfsdóttir, Annadís Greta; Gottfreðsdóttir, Helga
Abstract: In the last few decades, the demography of Iceland has become increasingly diverse with an immigrant population similar to that of the other Nordic countries. Women comprise almost half of all international migrants and many of those female migrants require maternity care in their host countries. While some literature describes how migrant women experience the healthcare provisions of their host countries, less is known about the experience of providing the service, from the perspective of the healthcare practitioners. In this study we adopt a social constructionist perspective to explore the discourses of knowledge healthcare professionals in Iceland draw on in their discussion of prenatal and postpartum healthcare in Iceland. Interviews were conducted with 16 healthcare professionals with extensive experience of providing maternity care to migrant women to understand how they construct and make sense of the needs and behaviour of migrant women seeking maternity care. Our findings suggest that some healthcare professionals subject migrant women to normative professional discourses of parenting, without considering how those ideals are tailored to white, middle class women. Migrant mothers and pregnant women are thus excluded from the middle-class mothering norms that are ascribed to Icelandic women. Our findings also highlight how national identity, such as being part of a gender equal society and the image of Iceland as a classless society, influences how healthcare professionals view migrant women. This underscores the importance of cultural reflexivity, and policies and scholarship where an intersectional understanding of gender, class and migrant worker status is at the forefront. Highlights: Interviews with healthcare professionals providing maternity care to migrant women. Distinctions are made based on lack of common ground and "us and them" dichotomy. Migrant mothers and pregnant women excluded from middle-class mothering norms. Equality and classlessness in national identity can become cultural "blind spots".